2021
DOI: 10.1002/mde.3293
|View full text |Cite
|
Sign up to set email alerts
|

The state‐level exemption changes in Chapter 7 protection and entrepreneurial activity in the United States

Abstract: To predict the effect of bankruptcy laws on entrepreneurial activity, we exploit the 2005 and 2011 staggered state‐level increases in exemptions for the amount of personal wealth protected under Chapter 7 bankruptcy in the United States. We focus on three types of outcomes—firm establishments, entrepreneurship quality, and individual self‐employment. Using state‐, cross‐border‐county‐neighbor‐pair‐, and individual‐level data, the additional state‐level exemptions do not affect any of the three types of entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, they could not produce notable results to justify their hypothesis. Patel and Devaraj [ 41 ] also examined the US state-level exemptions, their changes in legislation, and their effect on entrepreneurial activity. They concluded that entrepreneurial activity did not improve due to asset protection in personal bankruptcy systems.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, they could not produce notable results to justify their hypothesis. Patel and Devaraj [ 41 ] also examined the US state-level exemptions, their changes in legislation, and their effect on entrepreneurial activity. They concluded that entrepreneurial activity did not improve due to asset protection in personal bankruptcy systems.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It showed a positive impact from the homestead exemption on entrepreneurship development only among the states in the bottom quartile and otherwise highlighted a negative impact. Patel and Devaraj (2021) examined the state-level exemption changes in the US and their effect on entrepreneurial activity. However, their results did not support the view that asset protection in personal bankruptcy systems improved entrepreneurial activity.…”
Section: Literature Reviewmentioning
confidence: 99%